2021
DOI: 10.1007/s00438-021-01766-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome and translatome analyses reveal the role of protein extension and domestication in liver cancer oncogenesis

Abstract: One gene could be transcribed to different RNA isoforms, and then produce various forms of protein sequences. This mechanism largely diversifies the cellular pool and allows natural selection to select from a wider range of substrates. In the cancer field, the isoform switches between tumor and normal tissues, such as the alternative splicing, stop codon read-through, or protein domestication, are significantly ignored by the traditional differential expression analyses. The intention of this work is to fill t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Importantly, VEGF-Ax possesses anti-angiogenic activity opposite that of VEGF-A, and its expression is depleted in colon adenocarcinoma, suggesting that this translational readthrough event is manipulated by cancer cells to their advantage. Consistent with this notion, genomic-wide studies have revealed higher levels of stop codon readthrough in cancer cells (Wang and Wang, 2021). Although the detailed biochemical mechanism of stop codon readthrough remains to be deciphered, the fact that alteration of RQC activity can result in stop codon readthrough (Annibaldis et al, 2020), and that loss of a recently identified RQC factor EDF1 in yeast can result in frame-shifting at stall sites (Wang et al, 2018), suggests the potential involvement of RQC factors in this process.…”
Section: In-frame Stop Codon Readthrough and Frame-shifting In Cancer...mentioning
confidence: 88%
“…Importantly, VEGF-Ax possesses anti-angiogenic activity opposite that of VEGF-A, and its expression is depleted in colon adenocarcinoma, suggesting that this translational readthrough event is manipulated by cancer cells to their advantage. Consistent with this notion, genomic-wide studies have revealed higher levels of stop codon readthrough in cancer cells (Wang and Wang, 2021). Although the detailed biochemical mechanism of stop codon readthrough remains to be deciphered, the fact that alteration of RQC activity can result in stop codon readthrough (Annibaldis et al, 2020), and that loss of a recently identified RQC factor EDF1 in yeast can result in frame-shifting at stall sites (Wang et al, 2018), suggests the potential involvement of RQC factors in this process.…”
Section: In-frame Stop Codon Readthrough and Frame-shifting In Cancer...mentioning
confidence: 88%
“…Thus, correctly formed proteins are in general stable, whereas extended proteins are destabilized by triggering PQC, which protects the cell from potentially deleterious effects of non-natural proteins. The importance of the latter mechanism is underscored by increased translational read-through events that are detectable in tumor tissues ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…During long-term evolution, highly deleterious mutations have been eliminated and could no longer be seen at present time [ 25 ]. Beneficial mutations increase their frequency in natural populations [ 26 ] but the net gain of fitness is so subtle to be observed at phenotypical level [ 27 ]. This dilemma adds difficulty to the functional verification of mutations and makes the evolutionary theories hard to guide experimental biologists [ 28 ].…”
Section: Discussionmentioning
confidence: 99%